Activated prothrombin complex concentrate to treat bleeding events in acquired hemophilia A: BAHAS study. (12th September 2022) - Mingot‐Castellano, María E.; García‐Candel, Faustino; Benítez‐Hidalgo, Olga; Marco, Ana; Méndez Navarro, Gala A.; Pérez‐Montes, Rocío; García Donas, Gloria; Canaro, Mariana; Paloma, María J.; Asenjo, Beatríz; Calle‐Gordo, Victoria M.; González, Noelia P.; et al.
Abstract: Objective: Activated prothrombin complex concentrate (aPCC) is a bypassing agent indicated to treat bleeds in patients with acquired hemophilia A (AHA). Nevertheless, its efficacy and safety in the real‐world setting have not often been addressed. Methods: We report the experience of Spanish reference centers for coagulation disorders and from acquired hemophilia Spanish Registry (AHASR) from August 2012 to February 2021. Follow‐up period of 30 days after aPCC withdrawal. Results: Thirty patients with a median age of 70 years old, suffering from 51 bleeds treated with aPCC were finally evaluated. As first‐line treatment, aPCC stopped bleeding in 13 of 14 (92.9%) cases. aPCC as the second line after recombinant factor VIIa failure, stopped bleeding in all cases. In 17 patients, aPCC was used far from initial bleed control as prophylaxis of rebleeding with 94% effectiveness. No thromboembolic episodes were communicated. One patient developed hypofibrinogenemia, which did not prevent aPCC from halting bleeding. No other serious adverse events possibly or probably associated with aPCC were reported. Conclusions: This data support aPCC as hemostatic treatment in AHA with high effectiveness and excellent safety profile in acute bleeds and as extended use to prevent rebleedings, even in aging people with high cardiovascular risk.